Research on heat storage materials in solar thermal power system - Zhang Xudong (Functional Materials, 2019)
In this paper, through the collation and analysis of the literature related to phase change heat storage materials, the screening principle of the heat storage materials is proposed. Then the current hot spot molten salt and metal alloy phase change heat storage materials performance and research and development status are systematically summarized and analyzed. Finally, an economic analysis of thermal performance was performed. This paper has important reference value for the development and research of high temperature phase change heat storage technology for solar thermal power generation.